Bottom Trawling and Scallop Dredging in the Arctic : Impacts of fishing on non-target species, vulnerable habitats and cultural heritage - Guijarro Garcia, Elena; A. Ragnarsson, Stefán; A. Steingrímsson, Sigmar; Nævestad, Dag; Þ. Haraldsson, Haukur; H. Fosså, Jan; S. Tendal, Ole; Eiríksson, Hrafnkell; Skúladóttir, Unnur; Frandsen, Rikke; Siegstad, Helle (Copenhagen : Nordic Council of Ministers, 2007)
This project has been developed within the frame of the Nordic Action Plan 2000-2004 (Nord 1999:29) to review the status and threats of the natural and cultural heritage in Arctic waters. Two of the most commonly used demersal fishing gears in the Arctic are the otter trawl and the scallop dredge. Detrimental effects of bottom gear towed over the seabed include incidental catch and direct mortality of a wide range of organisms and habitat alteration. Any three-dimensional fragile structures rising above the seabed, such as cold-water corals, sponges, geological formations and archaeological remains are easily destroyed. This report reviews the scallop and shrimp fisheries, the distribution and conservation of vulnerable habitats (coral reefs, sponge communities), the status of archaeological remains on the seabed and relevant legislation and the conservation measures and role of protected areas. In addition there are two case studies based on fisheries and survey data from Iceland and recommendations to improve the current situation.